2019
DOI: 10.31674/mjn.2019.v11i02.006
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Barriers and Motivating Factors Influencing Research Productivity Among Nursing and Allied Health Professionals Trainers

Abstract: Introduction: Ministry of Health (MOH) Malaysia colleges, offer diploma and advanced diploma programmes for nursing, assistant medical officer and other allied health personnel. As academic institutions, the trainers are encouraged to participate and enhance the colleges' research productivity. The aim of this study is to explore the perceived barriers and motivation factors for research in MOH colleges. Method: A qualitative research design was conducted among MOH colleges trainers. Semi structured questions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The findings showed that around personal obstacles, the lack of time and business factor had the highest average score [20] The respondents of a research among academic staff at five Sudanese medical faculties reported "lack of allocated time" for research work as a barrier to research. Similarly lack of time due to teaching workload constitutes a hindrance to research in a Malaysian nursing school [21,22]. A study was conducted to identify barriers to research productivity among gastroenterologist in Saudi Arabia.…”
Section: Time Constraint For Researchmentioning
confidence: 99%
“…The findings showed that around personal obstacles, the lack of time and business factor had the highest average score [20] The respondents of a research among academic staff at five Sudanese medical faculties reported "lack of allocated time" for research work as a barrier to research. Similarly lack of time due to teaching workload constitutes a hindrance to research in a Malaysian nursing school [21,22]. A study was conducted to identify barriers to research productivity among gastroenterologist in Saudi Arabia.…”
Section: Time Constraint For Researchmentioning
confidence: 99%
“…First, while capabilities might include the skills of researchers to use software for qualitative and quantitative analyses, in our study, we have not measured their access to such software. Some studies consider such barriers significant to research productivity (see; Shanmugam et al, 2019;Teh et al, 2017). Second, we did not account for variations across different academic disciplines (see Albert, 2016), research collaboration (Nguyen, 2016), participation in academic associations (Valsangkar et al, 2016), and a responsible research climate .…”
Section: Conclusion Implications Extensions and Limitationsmentioning
confidence: 99%
“…Also, for not native speakers, proficiency in English might be a barrier (Tariq et al, 2016). Finally, the lack of mentorship within the faculty can be a substantial barrier (Shanmugam et al, 2019). Our purpose is to examine the effect of five significant barriers identified during the exploratory phase of the research, namely, access to research funds, teaching load, personal capabilities for carrying out research, personal interest in research and access to scientific articles databases.…”
Section: Introductionmentioning
confidence: 99%
“…Of concern is that nurses, clinical and academic, often face several barriers to doing research and publishing outcomes (Hagan et al, 2019 ; Shanmugam et al, 2019 ; White, 2013 ). In an Australian study, nurses' experiences of participating in academic‐led research, identified lack of organisational support and funding, and required resources for doing research as key barriers (Higgins et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%